Effects of Observing Urban and Natural Scenes on Working Memory Depletion and Restoration: An EEG Study - Lorenzo Consalvi; Kim Ouwehand; Fred Paas (Education Sciences)
Cognitive load theory focuses on the limited capacity of working memory (WM) to encapsulate information. While the original theory postulated a fixed capacity of working memory, research in the last decade has provided evidence for the depletion hypothesis. This hypothesis holds that WM becomes depleted after effortful cognitive operations that reduce its capacity, providing a framework for the restorative effects of rest periods. Rest periods during which natural scenery is observed have been found to replenish working memory after it has been subjected to depletion. In the present study, participants observed pictures depicting either a natural or an urban environment, after completing a cognitively depleting task. For this study, we obtained EEG measures of working memory by analyzing alpha and theta wave amplitudes. The motivation behind this choice was to derive a continuous index of WM capacity and address the lack of electrophysiological data regarding the depletion hypothesis. Previous research identified a decrease in alpha amplitude, and a simultaneous increase in theta activity with increasing WM load. Our findings partially replicated these results, as we observed a decrease in alpha amplitude with increasing cognitive load but no significant difference in theta power. Moreover, average signal amplitudes did not differ between the natural and the urban conditions, contrary to our hypothesis. These results suggest an absence of the expected environmental effect, opposing the outcome of existing research on the topic. The absence of this effect could also be attributed to similarities between the two conditions in certain factors thought to elicit differential physiological responses.